Careers in Programming How to Get a Great Coding Job (2019) - Jones, David (Packt Publishing, 2019)
Accelerate your coding career! Find a great job in programming or app development in a new course from Eazl & Codestars! About This Video Master strategy, résumé/CV writing, LinkedIn profile SEO, and coding interview preparation to achieve successful career advancement Ace whiteboard coding interviews and prepare a keyword-rich, targeted résumé that gets outstanding results In Detail A great job is key to living a happy life; however, the problem is, you know how competitive the job market is and you weren't taught to job hunt even though it is an essential skill. Don't worry! This course will take you through strategy, résumé;/CV writing, LinkedIn profile SEO, coding interview preparation, professional networking, salary negotiation, dealing with HR and recruiters, and much more. This course will not only guide you in gaining control of your career, but it'll also help you act with confidence and purpose so that you don't waste your valuable time and can earn more than you previously thought possible. Careers in Programming can make all this happen within a few weeks.